Generation of high brightness diode laser by using spectral and polarization beam combination. (August 2019) - Lin, Xunchun; Lin, Guyi; Zhao, Pengfei; Wang, Lirong; Yu, Haijuan
Highlights: The design combines spectral beam combination with polarization beam combination. Polarization beam combination improves the brightness limited by spectral beam combination. Equal optical path arrangement makes the design compact. Abstract: We present a beam combination technique to improve the brightness of diode lasers based on both spectral beam combination and polarization beam combination. We use eight diode laser arrays (DLAs) and two diffraction gratings to construct two independent external cavities by using spectral beam combination, and then combine the outputs of these two cavities by using polarization beam combination. The experiment shows that the total output power can be as high as 310.2 W by using this technique with eight DLAs, which are commercial standard cm-bars, each producing ∼60 W of output power. The beam qualities of the combined beam are M 2 = 13.55 and 10.27 in the slow and fast axis, respectively. The brightness of the combined output is as high as 252 MW·cm −2 ·sr −1 .